Genetic Variants and Haplotypes in OPG Gene Are Associated with Premature Coronary Artery Disease and Traditional Cardiovascular Risk Factors in Mexican Population: The GEA Study - Pérez-Hernández, Nonanzit (DNA Cell Biol, 2020)
Basic and clinical research have demonstrated that osteoprotegerin (OPG) plays an important role in the development and progression of cardiovascular diseases. The aim of this study was to evaluate the association of four polymorphic sites (rs2073618, rs3134069, rs3134070, and rs3102735) of OPG gene with premature coronary artery disease (pCAD), and with cardiometabolic parameters. The polymorphisms were genotyped using 5′ exonuclease TaqMan genotyping assays with real-time PCR in 1098 individuals with pCAD and 1041 healthy controls. rs2073618 polymorphism was associated with a high risk of developing pCAD according to different inheritance models: additive (p = 0.001; odds ratio [OR] = 1.283), dominant (p = 0.006; OR = 1.383), recessive (p = 0.011; OR = 1.423), and codominant 2 (p = 0.001; OR = 1.646). The four polymorphisms were associated with different cardiovascular risk factors in individuals with pCAD and controls. Our results suggest that OPG rs2073618 polymorphism is associated with an increased risk of pCAD. In addition, two haplotypes were associated with pCAD, one increasing the risk (CACT) and another one as protective (GACC).